The characteristic system for the Euler - Poisson's equations - Belyaev, A.V. (Нелинейные граничные задачи, 1999)
In this paper we investigate the nonlinear system naturally connected with the Euler - Poisson's equations. The solutions of this system may be used for description of the singular points to the Euler - Poisson's equations.